Trifluoromethylation of Disubstituted Morpholines by Metal-Free Visible Light Photoredox Catalysis - Srivastava1, Vishal; K. Singh2, Pravin; P. Singh3, Praveen (Asian Journal of Chemistry, 2016)
A mild and efficient one-pot visible light-induced method has been developed for the trifluoromethylation of disubstituted morpholines. This method includes synthesis of substituted 4-tosyl-5-[(trifluoromethyl)thio]morpholine 4(a-l) from tosylaziridine 1(a-l) and oxiran-2-thiol (2) in presence of eosin Y as an organophotoredox catalyst at room temperature under aerobic condition.